CYBER GOVERNANCE IN CHINA balancing state centrism and collaborative dynamics. - CAI, CUIHONG (ROUTLEDGE, 2025)
This book conducts an in-depth investigation into cyber governance in China through Chinese decision-making processes, policy formulation, and international presence, exploring how China navigates governance imperatives while fostering digital innovation in an increasingly interconnected world.The book looks at the governance paradigm of cyberspace in China. It examines the concepts, mechanisms, and practices predominantly spearheaded at the national level by the Chinese government, and the extensive participation of non-governmental entities. It unravels China's approach to cyber governance, why it diverges from Western approaches, and the causal mechanisms behind these phenomena through empirical research. The book also analyzes the strengths, deficiencies, and consequential impacts of China's cyber governance policies, utilizing social science research methodologies.This will be a book of interest to scholars in international relations, Internet governance, and China studies.
Keywords: Computer networks -- Law and legislation -- China.; Cyberspace -- Security measures -- Government policy -- China.; Computer security -- Law and legislation -- China.; elektronické knihy; electronic books